SNOM Imaging of a Crypt‐Like Feature in Adenocarcinoma Associated with Barrett's Oesophagus. Issue 4 (5th January 2018) - Craig, Timothy; Smith, Andrew D.; Holder, Gareth M.; Ingham, James; Smith, Caroline I.; Varro, Andrea; Pritchard, D. Mark; Barrett, Steve D.; Martin, David S.; Harrison, Paul; Wolski, Andrzej; Cricenti, Antonio; et al.
Abstract : The development of more accurate and sensitive diagnostic techniques is a key factor in efforts to improve cancer survival rates. The technique of infrared aperture fibre scanning near‐field optical microscopy (IR‐SNOM), together with radiation from the infrared free‐electron laser (IR‐FEL) on ALICE at Daresbury Laboratory (UK), has been used to obtain IR images of a crypt‐like feature and the surrounding tissue; the tissue was taken from a patient with oesophageal adenocarcinoma and with a history of Barrett's oesophagus. We have shown that the DNA signal is enhanced relative to other contributions in the region of the crypt, and the glycoprotein signal shows a less pronounced increase in the region of the crypt. The Amide II signal is found to be anti‐correlated with the DNA and glycoprotein profiles. The absorbance of the Amide II signal is found to differ for three different types of cancer tissue. High‐resolution IR images of the crypt reveal additional structure that would not be resolved in diffraction‐limited techniques. Abstract : Infrared scanning near‐field optical microscopy (IR‐SNOM) is used to image a crypt‐like feature from a patient with oesophageal adenocarcinoma and with a history of Barrett's oesophagus. The DNA signal is enhanced (red) relative to other contributions in the region of the crypt. High‐resolution IR images of the crypt reveal additional structure that would not be resolved in diffraction‐limited techniques.